Insights about the structure and development of Zhongsha Bank in the South China Sea from integrated geophysical modelling. Issue 7 (23rd May 2020) - Huang, Haibo; He, Enyuan; Qiu, Xuelin; Guo, Xingwei; Fan, Jianke; Zhang, Xunhua
ABSTRACT: We construct a complete density transection based on the velocity structures across the Zhongsha Bank in the South China Sea. Gravity modelling of the lateral density contrasts between tectonic units helps us to determine the structural attributes and boundaries between continental blocks and deep basins. The configuration of the continent–ocean boundary (COB) around the Zhongsha Bank is mapped based on the gravity/magnetic anomaly and crustal structures. A low-density mantle is found beneath the Zhongsha Bank and the oceanic basins, and this mantle is associated with the high heat-flow background. The COB orientation is northeast-east in the north of the bank, with faulted linear structures. In further southeast, where there is a more intact crust, the COB orientation changed to north-northeast. The reconstructed density model and gravity/magnetic map indicate that the Zhongsha Bank is conjugated with the Liyue Bank by a rifted basin, where the crust had experienced localized deformation before the seafloor spreading. Because of the insufficient magmatism in the oceanic basin, the spreading ridge propagates into the weakened continental lithosphere between the two continental blocks, thus completely separating the Zhongsha Bank from the Liyue Bank. Seafloor spreading ridge jumps within the South China Sea may also be affected by the heterogeneous lithosphere beneath the continental blocks and oceanic basins.